Effect of long day photoperiod and showering on milk yield and economic returns in Jaffrabadi buffalo - Savaliya, Bhagavanji Dayabhai (Indian Journal of Dairy Science, 2016)
Abstract       An experiment was conducted to  study the effect of long day photoperiod and two times showering on milk production, associative endocrine changes and their economic advantage in lactating Jaffrabadi buffaloes  between November, 2013 and May, 2014 at Cattle Breeding Farm, Junagadh Agricultural University, Junagadh. Twenty four recently calved Jaffrabadi buffaloes   (1-5 lactations) were randomized to four  groups of six each according to average   daily  milk  yield  and body   weight  for  a  total duration of 182 days.  The treatment groups were T1 (control-Natural day photoperiod-NDPP), T2 (NDPP + showering twice a day),     T3 (long day photoperiod of 18 h - LDPP) and T4 (LDPP + showering twice a day). The buffaloes were fed as per ICAR (2010) feeding standards to meet the nutritional demands of lactation. Supplemental lighting of 20 footcandle at eye level of buffaloes in T3 and T4 was provided by fluorescent lamps, controlled by automatic timer.  Buffaloes in T4 produced 27.68% (1.55 lit) more milk than control group of buffaloes, followed by T3 group of buffaloes producing 24.0% (1.35 lit) and T2 group of animals producing 8.93% (0.5 lit) more milk per day. Dairy farmer can earn an  additional  income of Rs. 9711 and Rs.13356 per buffalo per year (300 days) at farm prevailing price (Rs.36/l)  and at local market price (Rs.45/l) respectively in T3. The corresponding figures in T4  were Rs. 11630 and Rs.15798 respectively. Long day photoperiod along with showering twice a day produce synergetic effect on milk yield in Jaffrabadi buffaloes. They are simple to implement, easy to manage, profitable, cost effective and does not require any technological insertion in dairy buffalo management. Collectively, the efficiency of milk production in Jaffrabadi buffaloes can be enhanced through photoperiod manipulation and showering twice a day and thus, provide another management tool for dairy producers to enhance productivity and profitability.